The Legal Politics of Recall Right of Political Parties Relevance with the System of Popular Sovereignty In Dynamics of the Constitution of Indonesia - Malicia Evendia; Armen Yasir; Yulia Neta; Ade Arif Firmansyah (Faculty of Law, Pattimura University, 2020)
The existence of regulation of recall rights of political parties as regulated in Law No. 17 of 2014 and Law No. 2 of 2008 bring a great influence on the position of legislative members. Based on these rules, legislators may be dismissed from their positions if proposed by Political Party. This certainly brings a polemic for the people as the sovereign owner, who have chosen their representatives through the electoral process, but when chosen representatives of the people can be dismissed from his position by a political parties through the mechanism of the right of recall. This research was done by doctrinal method approach as well as the use of the statute, historical, and conceptual approach. This results showed that the legal politics of recall right of political parties is actually only used as an instrument of the political parties in controlling its members in parliament in order to always adhere to the party's policy direction. This makes the recall right political party is legal products that characterized conservative or orthodox. The existence of a political party's recall rights order gives a great authority to the political parties to negate the result of the people's choice as the holder of sovereignty for the sake of the political party. The function of political parties as a means of political recruitment in the process of filling political office in this case as members of the legislature, should have been completed after the people chose their representatives through electoral mechanisms. Therefore, it is necessary for the reconstruction of the ideal and relevant recall rights arrangement to the people's sovereignty.